Executive Committee Minutes 2018-02-22 - Academic Senate:::::::::
Agenda – Approved. Minutes of 2/8/18 lost. Chair Report. President Report. Emeritus Dinner. Revisions to the BS in Business – Approved for Senate consent calendar. Revision to the MA in Psychology – Approved for Senate consent calendar. Advising Task Force. Statewide Senator Report. Vice-Chair Report. APARC Report. EPC Report. FSAC Report. Senate meeting for March 1st cancelled due to lack of business. SAC Report. Associated Students Report.